Modified nanofibrillated cellulose (NFC) films: different strategies to enhance hydrophobicity and barrier to water vapor and oxygen - Souza, Gustavo de (2021)
Unmodified or modified nanofibrilated cellulose (NFC) can be employed to produce films by means of controlled drying processes to form compact three-dimensional networks, giving rise to low permeable and high strength films, with the potential to compete with synthetic polymers in packaging applications. However, due to the high hydrophilicity these films have applications limited to conditions of relative humidity below 60%. Above this value, water acts as a plasticizer, drastically reducing mechanical and barrier properties. The present work describes four strategies for obtaining hydrophobic and low permeable films to water vapor and oxygen. Three strategies involve chemical modification through the use of blocked isocyanates, being 1) superficial modification of the NFC film by dipping in solution; 2) obtaining films from a composition containing an aqueous suspension of NFC and an aqueous emulsion of a blocked (poly) isocyanate; 3) synthesis of a blocked polyethylene glycol diisocyanate and its use for the production of a composite where the matrix is formed by the PEG chains covalently bonded to the NFC reinforcement. For the three chemical modification strategies, the films were produced by casting and subjected to a thermal treatment to de-block the isocyanate. In strategy 4) a physical modification was proposed in which the films were formed by casting of a mixture containing an emulsion of beeswax and a suspension of NFC. Each strategy gave rise to a scientific paper that is presented individually. The set of published and not yet published papers makes up the present thesis. The physical properties (density and porosity), mechanical, morphological, thermal, water absorption, contact angle with water and water vapor and oxygen permeation were evaluated. In addition to the papers, a comparative discussion between the strategies is presented. In general, the proposed chemical and physical modifications were responsible for hydrophobization, increased water resistance and gas barrier properties, demonstrating the potential of the proposed strategies for the manufacture of high performance films in packaging whose raw material is from renewable source.